Carbon and Nitrogen Mineralization in Dark Grey Calcareous Floodplain Soil Is Influenced by Tillage Practices and Residue Retention - Nazmus Salahin; Md. Khairul Alam; Sharif Ahmed; Mohammad Jahiruddin; Ahmed Gaber; Walaa F. Alsanie; Akbar Hossain; Richard W. Bell (Plants, 2021)
Very little is known about the changes that occur in soil organic carbon (SOC) and total nitrogen (TN) under an intensive rice-based cropping system following the change to minimal tillage and increased crop residue retention in the Gangetic Plains of South Asia. The field experiment was conducted for 3 years at Rajbari, Bangladesh to examine the impact of tillage practices and crop residue retention on carbon (C) and nitrogen (N) cycling. The experiment comprised four tillage practices—conventional tillage (CT), zero tillage (ZT), strip-tillage (ST), and bed planting (BP) in combination with two residue retention levels—increased residue (R50%) and low residue (R20%—the current practice). The TN, SOC, and mineral N (NH4+-N and NO3−-N) were measured in the soil at different crop growth stages. After 3 years, ZT, ST, and BP sequestered 12, 11, and 6% more SOC, and 18, 13, and 10% more TN, respectively than the conventional crop establishment practice at 0–5 cm soil depth. The accumulation of SOC and TN was also higher compared to the initial SOC and TN in soil. Among the tillage practices, the maximum SOC and TN sequestration were recorded with ST and with R50% that might be attributed to reduced mineralization of C and N in soil particularly with increased residue retention, since decay rates of potentially mineralizable C was lower in the ST with both the residue retention practices. Increased residue retention and minimum tillage practices after nine consecutive crops has altered the C and N cycling by slowing the in-season turnover of C and N, reducing the level of nitrate-N available to plants in the growing season and increasing retained soil levels of SOC and TN.